Unveiling The Excellence: Socio-Cultural Perspectives on the Impact of Teacher Certification Program For Male Teachers In Indonesian Islamic Kindergartens - Tholchah, Muchammad (Faculty of Education and Teacher Training, Universitas Islam Negeri Walisongo Semarang, 2024)
There is a crucial importance to the quality of teachers in education, which necessitates strategies to ensure their competence. It is for this reason that teacher certification is utilized in Indonesia. In spite of the fact that existing research highlights its personal and pedagogical benefits, the socio-cultural dimensions of the initiative have yet to be adequately explored. Using sociocultural theory, this study conducted qualitative interviews with eight male teachers from Islamic kindergartens in four provinces in Indonesia. The analysis of these teachers revealed the following impact: certification increased their income, enhanced their institutional image within the community, provided opportunities for colleagues to share certification experiences, increased motivation to improve performance, and cultivated a spirit of collectivism by sharing certification benefits with non-certified colleagues. In addition to shedding light on income's pivotal significance in individuals’ lives, the certification program served as a cultural tool, power dynamics might be impacted by the certification program, and the program contributed to strengthening community values. As a result of this research, future studies may examine the program's long-term effects on teachers and the community in general, as well as its influence on power dynamics and cultural context.